THE NITRIC OXIDE SYSTEM IMBALANCE ROLE IN THE DEVELOPMENT OF ANTHRACYCLINE CARDIOTOXICITY IN ACUTE LEUKEMIA PATIENTS WITH CONCOMITANT ISCHEMIC HEART DISEASE - Лиманець, Т.В.; Маслова, Г.С.; Скрипник, І.М. (World of Medicine and Biology, 2016)
The article presents the own researches results of the leading pathogenetic ways determining of anthracycline-induced cardiotoxicity formation in patients with acute leukemia, depending on the presence of concomitant ischemic heart disease (IHD). The activation of aggressive oxygen species production is observed in all patients at the onset of acute leukemia with simultaneous antioxidant protection exhaustion. These processes are enhanced in the chemotherapy dynamics. In addition, there is an increased activity of summary NO-synthase in all patients with acute leukemia, that only in case of concomitant IHD is accompanied with the development of endothelial dysfunction, which creates conditions for deepening violations in the system of nitric oxide and consequently leads to heart tissue injury on a background of anthracycline antibiotics accumulation.
Keywords: acute leukemia; ischemic heart disease; anthracycline cardiotoxicity; nitric oxide; endothelial dysfunction